Detection of pesticide in a small agricultural basin after 15 years of application ban - Veselá, Tereza; null, null; Nedbal, Václav; Brom, Jakub (SGEM Scientific eLibrary, 2020)
Intensification of agriculture in order to increase efficiency and economic profitability brings about an increase in the input of foreign substances into the soil and surface water. The outflow of mineral fertilizers and pesticide residues can have a negative effect on organisms in the environment. High doses of fertilizers and pesticides also harm the quality of surface water, which is used for drinking water production. As a part of the research of a small sub-mountain agricultural catchment area, the specific runoff, the outflow of nitrate nitrogen (N-NO3-) and the outflow of pesticides were assessed. The catchment (363 ha) is located in the foothill area at an average altitude of 810 m with a mosaic of forests (38 %), meadows (38 %) and arable land (13 %). There were grown corn (23 ha), rape (8 ha) and barley (16 ha) in the observed period. The outflows of the substances were monitored during the vegetation season and during the high-intensity precipitation episode. The stable concentrations (0,24 ?g l-1 on average) of desisopropyl-atrazine (DIA) were found in the analysis of pesticides. The simazine was also detected in one case. DIA is a metabolite of atrazine, simazine or cyanazine. All these active substances used to protect maize have already been banned by European Commission in 2004. The results showed that both monitored pollutants (DIA and N-NO3-) were leaking into surface water from the soil during the entire monitored vegetation season and the precipitation episode. All detected DIA concentrations would exceed the limits for drinking water quality (0.1 ?g l-1) but didn't exceed the local limits for surface water quality. High correlations (R2 = 0.83 to 0.99) of the DIA outflow with the N-NO3- outflow and the specific runoff were found. Both pollutants flow rapidly from the catchment area into the watercourse due to their high solubility with increased precipitation totals. The main message of the work is, that pesticides residues persist in soil for years after cessation of their use and pollute surface waters. Due to the increase in frequency of high precipitation episodes in times of the climate change, the problem is growing. The solution will be a change of agricultural management and an improvement of landscape structure in the sense of better control of surface runoff.
Keywords: surface water, runoff, desisopropyl-atrazine, small basin, application ban